DEVELOPMENT OF LIFE SKILLS THROUGH PHYSICAL EDUCATION IN POSITIVE YOUTH DEVELOPMENT - Wardani, Fibrianti Kusuma; Ma’mun, Amung; Hendrayana, Yudy (ASEAN Journal of Sport for Development and Peace, 2021)
Life skills are defined as the range of transferable skills that all people need to help the process develop in daily life. Most definitions of life skills comment on differences between positive youth development and Life Skills. Sports-based life skills programs seek to foster positive youth development by teaching and promoting life skills in a sporting context. This article is a literature study that aims to review the description of life skills through physical education transferring in daily life and becoming a medium and vehicle for research by experts to develop life skills in the context of positive youth development. The results in this article attempt to describe the various studies conducted, including: first, the development of life skills through physical education in the context of PYD; Second, Life Skills in the framework of PYD for the future through physical education. These findings can be used as an inspiration for further research developments in the world of sports.